Knowledge levels of mothers with 0-3 years-old children about vitamin D and breast milk (Annals of Medical Research, 2023)
Aim: This study seeks to evaluate the awareness and knowledge levels of mothers with children younger than three years old about breast milk and vitamin D.Materials and Methods: A questionnaire containing 14 questions was administered to 405 women who applied to a district state hospital in Turkey. Analyses were conducted using the SPSS (Statistical Package for Social Sciences; SPSS Inc., Chicago, IL) 22.0 application.Results: The knowledge level of the mothers whose education level is high school and above was significantly higher than that of the mothers whose education level is secondary school and below (p=0.005). There was a significant difference between the economic status of mothers in terms of knowledge score (p
Keywords: Breast milk; Vitamin D; Level of knowledge; Awareness; Deficiency